Doing business in the Philippines 2008 comparing regulation in 21 cities and 178 economies. - International Bank for Reconstruction and Development; World Bank. (Washington, D.C. International Bank for Reconstruction and Development, 2008)
Doing business in the Philippines 2008 is a new subnational report of the Doing Business series in East Asia, following the Doing Business Report in China. Doing Business in the Philippines 2008 covers 21 cities that can be compared against each other, and with 178 economies around the world. The study includes 15 cities in Metro Manila: Caloocan, Las Piñas, Makati, Malabon, Mandaluyong, Marikina, Muntinlupa, Navotas, Parañaque, Pasay, Pasig, Quezon City, San Juan, Taguig, Valenzuela, 3 cities in the Visayas: Cebu, Lapu-Lapu and Mandaue, as well as Tanauan, and Davao. Comparisons with national results (as measured in Manila) and the rest of the world are based on the indicators in Doing Business 2008 and other subnational Doing Business reports.
Published jointly with the World Bank.
Keywords: Trade regulation -- Philippines; Industrial management -- Philippines; Business enterprises -- Government policy -- Philippines; Delegated legislation -- Economic aspects -- Philippines; Investments, Foreign -- Philippines; Philippines -- Commerce -- Handbooks, manuals, etc